Characterizations of novel konjac glucomannan emulsion films incorporated with high internal phase Pickering emulsions. (December 2020) - Liu, Zhe; Lin, Dehui; Shen, Rui; Yang, Xingbin
Abstract: This work attempted to develop novel high-barrier konjac glucomannan (KGM) emulsion films by high internal phase Pickering emulsions (HIPEs) incorporation approach. HIPEs prepared in this work were stabilized by bacterial cellulose nanofibers/soy protein isolation, displaying very stable properties, which were added into the KGM solution to prepare emulsion films. Meanwhile, the properties of the KGM-based emulsion films were investigated in the present work. The microstructures of KGM-based emulsion films presented that the HIPEs were uniformly distributed in the films, and the surface roughness of emulsion films was significantly increased with the increase of the emulsion/KGM ratios. Furthermore, the contact angle experiment suggested that the addition of HIPEs decreased the hydrophilicity of KGM films. Thermogravimetric analysis (TGA) showed that the thermal stability of all emulsion films was improved as compared with the pure KGM films because of the addition of HIPEs. In addition, the physical properties of all the emulsion films, including moisture content (MC), water solubility (WS), water vapor permeability (WVP), oxygen permeability (OP) and the mechanical properties, were improved as compared with the pure KGM films. Therefore, this study suggested that incorporating HIPEs was a promising pathway to improve the properties of pure KGM films. Graphical abstract: Image 1 Highlights: The high internal phase Pickering emulsions (HIPEs) displayed good stability. HIPEs could be well dispersed in konjac glucomannan (KGM) films. The physical properties of KGM films were improved by the addition of HIPEs. KGM-based emulsion films showed great potential as packaging films for food products.